Pengaruh Modal Kerja Dan Likuiditas Terhadap Profitabilitas - Siti Sarifah; Nesti Hapsari; Nana Diana (Journal of Economic, Bussines and Accounting (COSTING), 2021)
The purpose of this research is to find out and analyze the effect of working capital and liquidity on profitability, either partially or simultaneously. The method in this study uses descriptive and verification methods, this research begins by using the analysis of working capital as a variable Xâ‚. Then Liquidity as a variable Xâ‚‚. And finally Profitability as variable Y. The population in this study is all food companies and the minimum listed on the Indonesia Stock Exchange (IDX) in the period 2013-2019. The sampling technique used in this research is non-probability sampling with purposive sampling technique. Based on the sampling criteria as described above, the number of samples used in this study were 6 companies. The results of the research partially prove that the working capital variable has an effect on Return On Equity, the results of the partial test prove that the variable Current Ratio has an effect on Return On Equity and the research results simultaneously (together) Working Capital and Current Ratio have a significant effect on Return On Equity in food and beverage companies listed on the IDX for the period 2013-2019. Keywords: CR, Working Capital, ROA